Domestic violence and abuse: a reference handbook - Finley, Laura L. (Contemporary world issues Society, 2020)
"A comprehensive and timely resource for students, activists, educators and advocates, Domestic Violence and Abuse: A Reference Handbook provides a rich and scholarly assessment of this important social issue while also including stories and profiles for a more personal understanding. Domestic Violence and Abuse: A Reference Handbook provides a thorough review of the most recent research about intimate partner violence. Additionally, a historical review provides readers with a sense of how views on domestic violence have changed over time and how different policies and practices have and have not been successful. Appropriate for readers at the high school level and above, the volume focuses on the scope, extent, and characteristics of domestic violence and offers several unique elements, including profiles of significant individuals, personal stories from advocates, activists and survivors, and a review of controversial issues. The volume also includes a chronology of key events, relevant data and documents, primary source data, and recommended resources. --Compiles the most recent data about victims and offenders, thereby correcting many misconceptions about domestic violence --Offers a timeline of critical events for readers to understand the history of the movement --Includes primary source documents and personal stories, which help make the book beneficial to all readers --Addresses the most common controversies in the field, allowing readers to support more informed positions." --